PREVALENCE AND MANAGEMENT OF ANENCEPHALY AT SAIDU TEACHING HOSPITAL, SWAT - Khattak, Sania Tanweer; Khan, Muhammad; Naheed, Tabassum; Khattak, Imran ud Din; Ismail, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Anencephaly is a fatal congenital abnormality characterised by absence of cerebral hemisphere and cranial vault. Overall incidence of anencephaly is 3.8-6.0/1,000 births. This study was conducted to determine the prevalence, diagnosis and management of anencephaly in District Swat. Methods: This Prospective study was carried out over a period of one year from January 2007 to December 2007 at Saidu Teaching Hospital/Saidu Medical College Swat. Pregnant women having foetuses with neural tube defects (NTDs) admitted in Labour Room/Obstetric Ward of the Saidu Teaching Hospital Swat were selected as subjects. Those women who delivered normal babies were taken as control subjects. A proper history was taken from each subject and all the relevant information were recorded on a proforma. Results: A total of 5,560 subjects were included in this study. Out of them, 69 were having NTDs, 63 had anencephaly, 4 had spina bifida, and 2 foetuses were having multiple neural tube defects. Prevalence of anencephaly was 11.33/1000 births and that of spina bifida was 0.72/1000 births. Eighty percent (80%) anencephaly and 50% spina bifida were diagnosed by ultrasonography. Most of the cases (52, 75.36%) were delivered through normal vaginal delivery after induction. Twelve (17.40%) had spontaneous vaginal delivery, 4 (5.80%) had caesarean section, and hysterectomy was done in 1 (1.45%). Conclusion: Anencephaly is common congenital anomaly in Swat. Complications can be prevented by implementing screening program for early diagnosis, treatment, and management. Prevalence can be decreased by folic acid supplementation periconceptionally. Keywords: Anencephaly, Neural tube defects, prevalence, spina bifida